Application and research progress of the rapid rehabilitation concept in the perioperative gynaecological period - Wang, GaiJing; Cui, Jie; Wang, Xilian; Zhang, Yan; Liu, WeiHua; Ren, HaiMei (Frontiers in Oncology, 2025)
After 20 years of promotion and application, the concept of rapid rehabilitation (enhanced recovery after surgery [ERAS]) has penetrated various fields of surgery and achieved remarkable results. For example, in a recent case at our hospital, a 45-year-old patient with a benign uterine fibroid underwent laparoscopic myomectomy. Using ERAS protocols, she was discharged within 3 days compared with the traditional 7-day stay typically associated with open ovarian cystectomy. This highlights the potential benefits of ERAS in reducing hospital stays and improving patient satisfaction. In China, ERAS has been widely used in the fields of colorectal and hepatobiliary surgery, and related expert consensus has been formed, but it has not received sufficient attention in gynaecology. In 2016, the International Association of ERAS proposed guidelines for the application of ERAS in gynaecology/gynaecologic oncology. Therefore, to better understand and apply ERAS in gynaecology, this article reviews the progress of its application in perioperative gynaecology.